Congenital Cytomegalovirus Infection: Maternal–Child HLA-C, HLA-E, and HLA-G Affect Clinical Outcome - Rovito, Roberta; Claas, Frans H. J.; Haasnoot, Geert W.; Roelen, Dave L.; Kroes, Aloys C. M.; Eikmans, Michael; Vossen, Ann C. T. M. (Frontiers in Immunology, 2018)
Congenital CMV infection (cCMV) is the most common congenital infection causing permanent long-term impairments (LTI). cCMV immunopathogenesis is largely unknown due to the complex interplay between viral, maternal, placental and child factors. In this study, a large retrospective nation-wide cohort of children with cCMV and their mothers was used. HLA-C, HLA-E, and HLA-G were assessed in 96 mother-child pairs in relation to symptoms at birth and LTI at six years of age. The mothers were additionally typed for killer cell immunoglobulin-like receptors. The maternal HLA-G 14 bp deletion/deletion polymorphism was associated with a worse outcome, as the immunomodulation effect of higher proteins levels may induce less CMV control, with a direct impact on placenta and fetus. The absence of maternal HLA-C belonging to the C2 group was associated with symptoms at birth, as activating signals on decidual NK may override inhibitory signals, contributing to a placental pro-inflammatory environment. Here, the increased HLA-E*0101 and HLA-C mismatches, which were associated with symptoms at birth, may enhance maternal allo-reactivity to fetal Ags, and cause sub-optimal viral clearance. Finally, HLA-C non-inherited maternal antigens (NIMAs) were associated to LTI. The tolerance induced in the fetus towards NIMAs may indirectly induce a sub-optimal CMV antiviral response throughout childhood. In light of our findings, the potential role of maternal-child HLA in controlling CMV infection and cCMV-related disease, and the clinical value as predictor for long-term outcome certainly deserve further evaluation.